Case report: Anterior midline decompression of a cervical epidural abscess: Technical note and case series of seven patients - Zian, Ahmed; Arts, Mark P.; van der Gaag, Niels A. (Frontiers in Surgery, 2022)
Background Spinal epidural abscess (SEA) of the cervical spine is a relatively rare disease and generally characterized by progressive neurological deterioration due to spinal cord compression. Up to 40% of the cervical SAE are located ventrally of the spinal cord. Urgent surgical intervention is warranted to decompress the spinal cord and collect material for cultures to guide antibiotic treatment. However, optimal timing of the intervention is unclear, and the associated risk of spinal instability in the presence of an extensive infection poses a clinical dilemma. Methods In this paper we present a novel surgical technique to treat cervical SEA by an anterior decompression through a linear transvertebral midline approach. This technique has the advantage of effectively draining the ventrally located SEA and obtaining material for bacteria culture, while maintaining spinal stability without additional instrumentation. Results We present 7 patients with cervical SEA who were successfully treated with surgical decompression by this transvertebral linear midline technique and antibiotic treatment. Conclusion Anterior decompression through a linear transvertebral midline approach for ventrally located cervical SEA is a safe and pragmatic surgical procedure to achieve spinal cord decompression and collect bacteria culture, without destabilizing the spine.